Bridging the Gap between Single Nanoparticle Imaging and Global Electrochemical Response by Correlative Microscopy Assisted By Machine Vision. Issue 9 (5th July 2022) - Godeffroy, Louis; Lemineur, Jean‐François; Shkirskiy, Viacheslav; Miranda Vieira, Mathias; Noël, Jean‐Marc; Kanoufi, Frédéric
Abstract: The nanostructuration of an electrochemical interface dictates its micro‐ and macroscopic behavior. It is generally highly complex and often evolves under operating conditions. Electrochemistry at these nanostructurations can be imaged both operando and/or ex situ at the single nanoobject or nanoparticle (NP) level by diverse optical, electron, and local probe microscopy techniques. However, they only probe a tiny random fraction of interfaces that are by essence highly heterogeneous. Given the above background, correlative multimicroscopy strategy coupled to electrochemistry in a droplet cell provides a unique solution to gain mechanistic insights in electrocatalysis. To do so, a general machine‐vision methodology is depicted enabling the automated local identification of various physical and chemical descriptors of NPs (size, composition, activity) obtained from multiple complementary operando and ex situ microscopy imaging of the electrode. These multifarious microscopically probed descriptors for each and all individual NPs are used to reconstruct the global electrochemical response. Herein the methodology unveils the competing processes involved in the electrocatalysis of hydrogen evolution reaction at nickel based NPs, showing that Ni metal activity is comparable to that of platinum. Abstract : A machine‐vision methodology is depicted enabling the automated identification of various descriptors of ≈1000 individual nanoparticles (size, position, composition, activity) obtained from multiple complementary operando optical monitoring and ex situ microscopy imaging of electrochemical reactions. Comparing the contribution of all individual nanoparticles with the electrochemical response unveils the electrocatalysis of hydrogen evolution by Ni metal.